2005
DOI: 10.1093/cercor/bhi053
|View full text |Cite
|
Sign up to set email alerts
|

Neural Systems Underlying Observation of Humanly Impossible Movements: An fMRI Study

Abstract: Previous studies have indicated that largely overlapping parts of a complex, mainly fronto-parietal, neural network are activated during both observation and execution of an action. If these two processes are inextricably linked, increases of neural activity contingent upon action observation should be found only for movements that can actually be performed. Using functional magnetic resonance imaging, we investigated whether observation of possible and biomechanically impossible movements of fingers activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
107
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 40 publications
18
107
1
1
Order By: Relevance
“…This insensitivity to the difference in movements is consistent with recent neuroimaging and physiological evidence presented by Aglioti and colleagues (Costantini et al, 2005;Romani, Cesari, Urgesi, Facchini, & Aglioti, 2005). Using fMRI, these researchers found similar activation of premotor mirror system regions elicited from observation of biomechanically possible and impossible actions (Costantini et al),; while using TMS, they found similar cortiospinal excitability elicited by the observation of possible and impossible finger movements Imitation of Impossible Movements 17 (Romani et al).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This insensitivity to the difference in movements is consistent with recent neuroimaging and physiological evidence presented by Aglioti and colleagues (Costantini et al, 2005;Romani, Cesari, Urgesi, Facchini, & Aglioti, 2005). Using fMRI, these researchers found similar activation of premotor mirror system regions elicited from observation of biomechanically possible and impossible actions (Costantini et al),; while using TMS, they found similar cortiospinal excitability elicited by the observation of possible and impossible finger movements Imitation of Impossible Movements 17 (Romani et al).…”
Section: Resultssupporting
confidence: 90%
“…On the one hand, the behavioral results from Experiment 1 dovetail with recent fMRI (Costantini et al, 2005) and TMS findings that biomechanically possible and impossible actions are coded similarilysimilarly by mirror/common coding mechanisms; on the other, the results of Experiment 2 are consistent with recent behavioral (Casile & Giese, 2006), developmental Sommerville, Woodward, & Needham, 2005), and neuroimaging (Buccino et al, 2004;Calvo-Merino et al, 2005Costantini et al, 2005) studies relating the representation of perceived actions to the observer's own ability to perform the action. Calvo-Merino and colleagues (2006), for example, presented expert ballet dancers with examples of dance moves that either were in their own motor repertoire or were performed only by opposite-gender dancers, finding increased activation in mirror circuits for the samegender moves.…”
Section: Attentional Weighting Effects On Automatic Imitationsupporting
confidence: 81%
“…Action observation and execution increases neural activity in both motor and somatosensory areas [Rizzolatti and Craighero, 2004]. Crucially, making the perceived action painful or more salient from a tactile or proprioceptive point of view causes an increase of the activity in SI Betti et al, 2009;Bufalari et al, 2007;Costantini et al, 2005]. A recent study demonstrated that TMS over SI selectively reduced the typical corticospinal mapping of biomechanically impossible movements [Fadiga et al, 1995[Fadiga et al, , 2005Romani et al, 2005], which were associated with aversive somatic feelings, without impacting mirror responses to possible movements that did not evoke somatic feelings in the observer.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent research, numerous further issues about the human MNS have been explored, for example its lateralization (Aziz-Zadeh, Koski, Zaidel, Mazziotta, & Iacoboni, 2006;Mü hlau et al, 2005), inhibitory mechanisms (Alegre, Lazaro, Valencia, Iriarte, & Artieda, 2006;Brass, Derrfuss, & von Cramon, 2005), perspective effects (Jackson, Meltzoff, & Decety, 2006;Koski, Iacoboni, Dubeau, Woods, & Mazziotta, 2003), motor versus visuospatial representations (Chaminade, Meltzoff, & Decety, 2005), and the extent to which robot-like (Tai, Scherfler, Brooks, Sawamoto, & Castiello, 2004;but see Press, Bird, Flach, & Heyes, 2005) or biomechanically impossible displays (Costantini et al, 2005) elicit activations in the MNS. A further focus of current research is the conspicuous multifunctionality of the human inferior frontal gyrus beyond action recognition and imitation.…”
Section: The Human Mirror Neuron System and Imitationmentioning
confidence: 99%